EXPLORING EFL LEARNER'S SELF-EFFICACY, BELIEFS AND METACOGNITIVE STRATEGIES USE TO ENHANCE THE ENGLISH PROFICIENCY IN INDONESIA - Muslikan, Muslikan (LUNAR, 2017)
Individual differences among EFL learners have been widely accepted playing important roles on successful English learners. EFL teachers should encourage the language learners to improve their self-efficacy and language learning strategy use especially metacognitive by seeking the ways to increase their experience or years of English study. This also should necessarily result in change in their beliefs and learning strategy use especially about foreign language learning because people with high self-efficacy—that is, those who believe they can perform well—are more likely to view difficult tasks as something to be mastered rather than something to be avoided. Moreover, metacognitive strategies are needed for planning, monitoring, and evaluating learning. Started from this understanding, it can be widely believed that both learners’ self-efficacy and metaconitive strategy are undoubtedly powerful variables on enhancing the learners’ English proficiency. Thus, this paper will focus on exploring EFL learner's self-efficacy beliefs and metacognitive strategies use to enhance their English proficiency.